Ultrasound investigation in estimation of vascular invasion and morphological verification of pancreatic tumors - S. O. Stepanov; N. A. Rubtsova; D. V. Sidorov; L. O. Petrov; L. A. Mitina; V. I. Kazakevich; Ye. N. Slavnova; E. V. Prozorova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of publication. To present potential of ultrasound investigation (US) in diagnostics of pancreatic tumors (PT).Summary. Morphological verification of PT and estimation of stage of their progression are the basic factors of treatment planning. Traditionally «the gold standard» in detection of tumor and estimation of vascular invasion is computer tomography. In world practice US at PT is used only at the stage of primary diagnostics, as a rule, application at specifying diagnostics stage is limited because the method is operator-dependent and storage of study data is complex. However US can be carried out in various planes and positions of the patient’s body, that in some cases helps to receive additional information. Though morphological verification is the leading factor in assessment of prognosis and treatment approach at oncologic diseases, its necessity and ways of tissue sampling at PT is discussed up to now.Conclusion. Potential of US in morphological verification and assessment of vascular invasion of PT is demonstrated by the clinical case example, that has allowed to carry out radical surgical treatment to the patient.